Quality and microbiological safety of a daily mortality compost produced in a veterinary faculty at São Paulo state - Villamizar Cancelado, Sonia (Innovaciencia, 2021)
Introduction: Daily and outbursts mortality composting have been identified as one of the finest methods for final disposal of animal corpses, but the probable threat of pathogens transmission truly limits its use. Materials and Methods:  In this study we evaluated the quality and microbiological biosafety of a compost produced in daily mortality experimental unit composting at the Universidade Estadual Paulista in the state of Sao Paulo, Brazil. Settled compost sample was evaluated in order to determine the presence and counting of coliforms and Salmonella sp. and the pathotypes of E. coli STEC, EPEC and EHEC using culture and molecular techniques.  The occurrence of frequent soil borne phytopathogenic fungi was also estimated using selective and differential microbiological culture media. Results and Discussion: The occurrence of pathogenic E. coli, Salmonella sp and phytopathogenic fungi were negative. Coliforms level was 3.05 log10/g. Conclusions: The results showed that daily mortality composting method is effective to reduce pathogenic microorganisms, however, in order to add the product on crops or plants such as vegetables that are for direct human consumption, additional tests must be performed to assess the presence of viral pathogens and endospores forming bacteria.
Keywords: Daily Mortality; Composting; Coliforms; enteropathogenic E. coli